Innovative Teaching with Yasaro Method: Enhancing Qur'an Translation for Elementary Students - Rahma Aulia Nurcholis; Banu Setyo Adi; Setiawan Edi Wibowo (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to evaluate the effectiveness of the Yasaro method as an innovative approach to enhancing students' understanding of the Qur'an at the primary education level. The Yasaro method focuses on teaching Qur'anic translation word by word and is implemented among early-grade students at Muhammadiyah Elementary School in Temanggung Regency. A qualitative descriptive approach was employed, utilizing a case study design. Data collection involved classroom observations, in-depth interviews with teachers and students, and analysis of learning documents. The study sample consisted of 65 second-grade students and one teacher. The findings indicate that the Yasaro method significantly improved students' comprehension and memorization of Qur'anic verses, particularly in mastering the meaning and recitation of Surah Al-Ma'un. However, several challenges were identified, including limited instructional time, classroom management difficulties, and minimal parental support for at-home learning. To address these challenges, the study recommends optimizing collaboration between teachers and parents and incorporating a wider range of learning media to enrich the instructional process. Overall, the research highlights the Yasaro method's potential as an effective and age-appropriate strategy for Qur'an instruction at the elementary school level, offering valuable insights for future development of innovative religious education methods.